Strategi Pembelajaran: Penerapan Quantum Teaching and Learning dalam Penanaman Karakter Siswa Sekolah Dasar Abad 21 - Fajriyatur Robi’ah; Ikhsan Fitrian Catur Nugraha; Mochamad Cepi Firmansyah; Prihantini Prihantini (Peneliti.net, 2022)
Education is always aimed at increasing students' understanding of a material without prioritizing the student's character which will be the key to future changes. This study aims to find out learning strategies that can instill students' character according to the challenges of the times they face. This study uses a descriptive research method with a qualitative approach. The authors carry out research steps by collecting and analyzing data related to the discussion based on various literative sources, then the facts of events that have been written in the statements are revealed to be a conclusion. The results of the study conclude that changes in student character that occur due to the development of the times require teachers to look for strategies to deal with them, namely by applying quantum teaching and learning